Piezoelectric generator design and aerodynamic analysis. (March 2014) - Nie, W. R.; Xi, Z. W.; Lu, X. S.; Huang, L.; Zhou, Z. J.
Abstract : A piezoelectric generator is proposed in this paper that transforms aerodynamic energy to electrical energy. This new energy transducer takes a structure of resonant cavity and cantilever beams, which is stimulated by airflow when projectile is in flight. The cantilever beams are covered with piezoelectric thin films. When the stimulating frequency is equal to or approximate to resonant frequency of the cantilever, higher voltage would be produced. Analysis and simulation has been done based on finite elements method. This paper optimises the structure of cantilever beams, pneumatic cavity unit and whole generator. The final structure has a small volume, 3×1·5×1 mm. The piezoelectric vibrators can generate maximum open circuit voltages 8·59, 5·418, 4·095 and 3·691 V respectively when they work in their resonant frequency from 2700 to 6500 Hz.